2023
DOI: 10.3390/aerospace10010061
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Commercial Best Practices to U.S. Air Force Maintenance Scheduling

Abstract: This paper presents how the Inspection Development Framework’s (IDF) novel maintenance scheduling technique increased aircraft utilization and availability in a sample of the United States Air Force’s (USAF) C-5M Super Galaxy fleet. The hypothesis tested was “Can we execute segmented maintenance requirements during ground time opportunities in order to optimize flying?” We applied IDF to decompose the C-5M’s five‑day Home Station Check (HSC) inspection into smaller work packages that subordinate to operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…It requires an agile supply chain supporting a maintenance and repair enterprise that dynamically schedules maintenance actions driven by comprehensive data feeds and state-of-the-art prognostic failure models. To contextualize the KC-46A desired CBM+ future state, the KC-46A SPO, Georgia Tech Research Institute (GTRI), and Delta TechOps studied how Delta achieved success in its predictive maintenance activities as a leading B767 commercial operator [5,6]. Specifically, the research collaboration investigated how Delta TechOps participated in industry activity with the FAA, OEMs, and other commercial operators to demonstrate and certify CBM+ improvements as an alternate means of compliance (AMOC) for maintenance requirements.…”
Section: Department Of Defense (Dod) Cbm+mentioning
confidence: 99%
“…It requires an agile supply chain supporting a maintenance and repair enterprise that dynamically schedules maintenance actions driven by comprehensive data feeds and state-of-the-art prognostic failure models. To contextualize the KC-46A desired CBM+ future state, the KC-46A SPO, Georgia Tech Research Institute (GTRI), and Delta TechOps studied how Delta achieved success in its predictive maintenance activities as a leading B767 commercial operator [5,6]. Specifically, the research collaboration investigated how Delta TechOps participated in industry activity with the FAA, OEMs, and other commercial operators to demonstrate and certify CBM+ improvements as an alternate means of compliance (AMOC) for maintenance requirements.…”
Section: Department Of Defense (Dod) Cbm+mentioning
confidence: 99%
“…Li et al estimated the number of maintenance personnel by analyzing the task size [11]. Zhu, et al comprehensively considered various kinds of operation, shift preparation, and other factors, and obtained the standard staffing number of vehicle service systems, which provided a theoretical basis for operating enterprises to reserve personnel in advance [12]. Wang found that the reasonable allocation of the hospital's own medical equipment maintenance technical force is an important means to improve the comprehensive benefits of the hospital [13].…”
Section: Introductionmentioning
confidence: 99%